From Alienation to Revolution: Female Characters as Decolonial Tools in J.L. Torres’s The Accidental Native - Martínez Reyes, Consuelo (Revista Canadiense de Estudios Hispánicos, 2021)
In J.L. Torres’s The Accidental Native (2013), Rennie moves back to his native Puerto Rico after being raised in the United States. There, he meets his true biological mother, as well as his future (female) partner. Rennie’s unawareness of his mother’s existence and Puerto Rico’s colonial situation, as well as his partner’s illness, interweave maternal and romantic love with the Island. Furthermore, their ties pre-configure the birth of Rennie’s decolonial consciousness. This analysis dialogues with representations of the United States as an oppressive patriarchal figure to the Island, its inept child, in order to incorporate and contrast the role of the mother, as well as other affective figures, within the long tradition of genealogical metaphors in the Island’s literature. A decolonial interpretation of J.L. Torres’ work proposes a familial configuration in which affective forces originating from female characters function as a tool of epistemic liberation against imperialist, colonizing, patriarchal powers, thus proposing theoretical ties between affective and decolonial studies.